The Development Of Visual Aspects In Video Games Over The Years - Christian Aditya (ULTIMART Jurnal Komunikasi Visual, 2014)
This report investigates the importance of creating a realistic environment in order to create an immersive world in digital games. The discussion will start from the history of Digital game development until now, discussing on the limitations of gaming consoles from time to time, and how game designers nowadays keep pushing the boundaries of the visual aspects of their game. Then focusing the discussion on the technical and art aspect of digital game design. By doing the analysis in this report, we can conclude that there are several reason that affects the visual quality of video games, such as the technology of the game console, the limitation of game engine, and also the skill of the game artist itself. Key words : Video Games, Digital Games, Game Console, Environment, Game Engine.